THE PRAGMATIC FUNCTIONS OF EXPRESSIVE LANGUAGE IN ENGLISH SOCIAL MEDIA COMMUNICATION - Bekberganova, Khilola; Nazarov, Murod (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
In the digital age, social media platforms have revolutionized English-language communication, with expressive language—encompassing emojis, slang, profanity, and emotive speech acts—serving crucial pragmatic functions. This thesis explores these functions, drawing on scholarly analyses to demonstrate how expressive elements facilitate emotional conveyance, social bonding, persuasion, and intent revelation in online interactions. Through a pragmatic lens, including speech act theory and implicature analysis, the study reveals that expressive language in English social media not only compensates for the absence of nonverbal cues but also enhances user engagement, fosters rapport, and sometimes violates politeness maxims to achieve communicative goals. Key insights include the role of emojis as illocutionary force indicators, slang's contextual adaptability in gaming communities, and profanity's cathartic and abusive purposes. Utilizing data from platforms like Facebook, Instagram, and online health communities, the analysis underscores variations across age groups, cultural contexts, and thematic discourses (e.g., political, health-related). Findings indicate that expressive language boosts cognitive and emotional resonance in digital dialogues, with implications for digital literacy, behavior change interventions, and cross-cultural pragmatics. This work contributes to understanding how social media reshapes linguistic pragmatics, promoting more effective online communication strategies.